Assessing the Enforceability of The Right to Freedom from Gender Discrimination in Nigeria - Eruteya, Ugiomo (Universitas Negeri Gorontalo, 2024)
Gender-based biases remain pervasive in Nigeria, manifesting in restricted access to education, employment, healthcare, unequal pay, and sexual harassment. Despite the 1999 Nigerian Constitution's guarantee of freedom from discriminatory practices and Nigeria's commitment to regional and international human rights instruments promoting gender equality, women and girls in the country continue to face significant mistreatment. This discrimination results in economic deprivation, social inequalities, and other forms of abuse, all hindering sustainable development. This study employs a doctrinal legal research methodology to explore the challenges in enforcing gender equality laws in Nigeria. It identifies key factors obstructing the effective implementation of anti-discrimination measures, including insufficient enforcement mechanisms, lack of awareness and education, and the failure to domesticate and fully implement gender-sensitive laws and policies. The study highlights the importance of domestication and full implementation of international instruments like the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) as crucial steps toward overcoming these barriers. This study recommends stricter law enforcement, increased educational outreach to rural women, and the domestication of CEDAW and other gender-equal laws that remain unenforced in Nigeria. This research underscores the urgency of addressing legal and social barriers to gender equality, critical to the nation's development and the protection of women's human rights.